RELATIONSHIP BETWEEN PUPAL DIMENSIONS AND FECUNDITY IN TASAR SILK WORM, ANTHERAEA MYLITTA DRURY (LEPIDOPTERA : SATURNIIDAE) - BAIDHERA, SANGEETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
In females of Antheraea mylitta Drury, the number of eggs laid was correlated with the pupal measurements like pupal weight, abdominal length and abdominal girth. All the measurements considered were found to be genuine estimator of the fecundity, however, the pupal weight was the best estimator of fecundity.